ICU nurses´ lived experience of caring for adult patients with a tracheostomy in ICU: a phenomenological-hermeneutic study - Abder Rahim Akroute; Berit Støre Brinchmann; Anders Hovland; Sven-Tore Dreyer Fredriksen (BMC, 2022)
Abstract Background The care of adult patients with a tracheostomy in intensive care unit is complex, challenging and requires skilled intensive care unit nurses. ICU nurses' live experience is scarcely known. This study aimed to describe the lived experience of intensive care unit nurses of caring for adult patients with a tracheostomy in intensive care unit. Methods This study employs a qualitative design. In-depth interviews were conducted with a purposive sampling of 6 intensive care unit nurses from a medical-surgical ICU of a university hospital in Norway who were interviewed. Data was analyzed and interpreted using a phenomenological-hermeneutic approach. This study was reported according to the Consolidated Criteria for Reporting Qualitative Research (COREQ). Results The interpretation yielded the following themes and subthemes: 1) theme: 'challenges of caring for patients with a tracheostomy' consisted of the sub-themes: 'difficult to communicate/interpret and understand the patient's different forms of expression', 'complicated professional assessments', 'caring with patience', and 'collaborating with patient regarding challenges. 2) theme: 'the satisfaction from providing care to patients with a tracheostomy' consisted of the sub-themes: 'working with intensive care patients is instructive' and 'importance to motivate'. Conclusions ICU nurses experienced ambivalent feelings while caring for adult patients with a tracheostomy in ICU. They perceived caring as demanding owing to communication and collaboration at the same time, they experienced satisfaction while they strived to provide proper care and motivation. The identified challenges would lead to further improvement in nurses' experiences and, in turn, the quality-of-care for patients with a tracheostomy. Awareness of these challenges is crucial to understand the need for an effective communication strategy to improve the quality and safety of adult patients with tracheostomy in ICU.